(untitled) (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
The British colonial enterprise in Nigeria, no doubt is the most studied aspect of the country’s History. The subject had attracted both national and international scholars and has been studied from different approach and perspectives. Nonetheless, much attention has not been given to the implication arising from the incorporation of Northern Nigeria into the global capitalist economy on Small Scale Societies. It is against this backdrop that the paper attempts a study on the socio-political implication on Bwazza Society after the creation of the Native Authority System. Using both primary and secondary sources the study finds, that Bwazza Chiefdom was reduced to a village and the people reduced to ‘minority’ as a result of creation of the Native Authority System in Numan Division.